Operational tolerance research in liver transplantation: a bibliometric analysis using a new web resource - Esteban-Gil, Ángel; Martínez-García, Juan José; Vidal-Correoso, Daniel; Muñoz-Morales, Ana M.; Ramírez, Pablo; Pons, José Antonio; Baroja-Mazo, Alberto (Frontiers in Research Metrics and Analytics, 2024)
Background: Operational tolerance in liver transplantation (OT-LT), defined as the graft survival with normal function in absence of immunosuppression, has been a field of intense research since the 1980s. Thereafter, tens of clinical trials and hundreds of articles have been published, making it challenging for researchers to assimilate all the information, more so outside of their disciplines. The aim of the present study was to analyze the research in OT-LT through a new web tool (https://tolerance.imib.es). Methods: We have developed a web resource that allowed the identification of the present trends and potential research avenues in OL-LT, an overview biomedical terms that were most often cited, including which journals published the most articles, and an advanced search engine that exploited all the information in these publications. Results: A total of 734 studies were analyzed until November 2023, with a mean of 15 articles published per year, a total sum of 3,751 impact factor points and a total of 26,542 citations. The analysis of citations allowed us to establish a ranking of the most prolific countries, authors, journals and institutions, in addition to the most influential publications in OT-LT. Likewise, keyword and co-occurrence analyses answered which themes involving OT-LT are the most popular, whereas cooperation analysis showed that principal authors in OT-LT form a network, although the lack of international cooperation, especially with regard to clinical trials, appears to be one of the main challenges. Conclusion: Despite its limitations, our web tool will allow both OT-LT expert and novel researchers to be able to draw a comprehensive picture of the past, present and future of OT-LT research.